2004
DOI: 10.5254/1.3547825
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Crystallization Properties of Natural and Synthetic CIS-Polyisoprene

Abstract: Stress-induced crystallization and melting of natural and synthetic cis-isoprene are compared by simultaneous Wide Angles X-ray Scattering (WAXS) and mechanical measurements. Natural (NR) and synthetic polyisoprene (SR) rubbers have the same composition and sulfur crosslink density. At fixed elongation and during cyclic deformation, the properties X of the semi crystalline phase are determined as function of draw ratio λ; X being crystallites dimensions and orientation, half-time of crystallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 0 publications
5
64
1
Order By: Relevance
“…2,3 The higher T m of NR, not only in unstretched but also in stretched states, has been experimentally confirmed by Gent et al, 43 and recently by Trabelsi et al 42 Poompradub et al 44 further discussed this feature on the basis of the synchrotron WAXD studies for filled NR samples. They reported that the i values were also independent of the filler content, if the effective strain ratio of deformable rubber portion was taken into account.…”
Section: Incipient Strain Of Crystallizationmentioning
confidence: 73%
See 4 more Smart Citations
“…2,3 The higher T m of NR, not only in unstretched but also in stretched states, has been experimentally confirmed by Gent et al, 43 and recently by Trabelsi et al 42 Poompradub et al 44 further discussed this feature on the basis of the synchrotron WAXD studies for filled NR samples. They reported that the i values were also independent of the filler content, if the effective strain ratio of deformable rubber portion was taken into account.…”
Section: Incipient Strain Of Crystallizationmentioning
confidence: 73%
“…42,46,51 This fact indicates that the increase in crystallinity is due to the increased number of crystallites whose average size is constant. The crystallite size is slightly smaller for the samples with the larger .…”
Section: Morphological Featuresmentioning
confidence: 97%
See 3 more Smart Citations